Electromagnetic propagation through non-dissipative and dissipative barriers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Physics at Massey University, Palmerston North, New Zealand - Shalav, Avi (Massey University, 2002)
A Matlab simulation was developed to help visualise and investigate electromagnetic tunnelling through particular non-dissipative and dissipative barriers within a waveguide. The theory behind the simulation is based on a transmission line model that accurately predicts experimental results and is shown to be equivalent to previous numerical and quantum tunnelling models. A few useful speeds referring to electromagnetic waves have been defined and utilised to calculate die speeds at which different incident time signals penetrate electromagnetic barriers. Due to bandwidth restrictions, the created incident time signals had wavepacket properties. The importance of resampling an oscillating signal at the appropriate frequency to avoid aliasing has been recognised. The definition and creation of matched signals that can penetrate long barriers yet remain a single pulse have been investigated. Such signals will have no practical application since the attenuation will deem the transmitted signals immeasurable. However, the speeds through these larger barrier lengths will have a smaller uncertainty since the time delays are longer. Most of the signal distortion depends only on the barrier interfaces rather than the barrier length. Penetration through dissipative barriers gives speeds below the vacuum speed of light for all barrier lengths investigated. Faster than light speeds are however predicted for penetration through non-dissipative barriers greater than about 4cm.
Keywords: Electromagnetic waves